2015
DOI: 10.1007/s12040-015-0590-9
|View full text |Cite
|
Sign up to set email alerts
|

Water–rock interaction on the development of granite gneissic weathered profiles in Garhwal Lesser Himalaya, India

Abstract: The development and sustainability of weathered profiles are very difficult in the Himalaya due to its complex lithology, tectonic history and fast erosion. Despite this, two weathered profiles namely WPa (weathered profile a) and WPb (weathered profile b) which have sustained erosion are developed on porphyry granite gneiss and granite gneissic lithology in Alaknanda valley of the Garhwal Lesser Himalaya. Systematic sampling of these two weathered profiles was done from bottom to top and they were chemically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Uranium concentrations observed in the lake water and ice samples from the present study are within the range reported for lakes near McMurdo Dry Valleys (Henderson et al, 2006). The sources of U in the lake water in the study area are mainly from deposition of the sea-salt aerosols and rock/soil-water interactions (Röthlisberger, 2002;Vyshnavi & Islam, 2015). The mean tritium concentration in the lakes of Larsemann Region is around 1.3 Bq/L which is much less than observed by Pourchet et al (1997) as shown in Table 6.…”
Section: U and 3 H In Lake Water And Icesupporting
confidence: 80%
“…Uranium concentrations observed in the lake water and ice samples from the present study are within the range reported for lakes near McMurdo Dry Valleys (Henderson et al, 2006). The sources of U in the lake water in the study area are mainly from deposition of the sea-salt aerosols and rock/soil-water interactions (Röthlisberger, 2002;Vyshnavi & Islam, 2015). The mean tritium concentration in the lakes of Larsemann Region is around 1.3 Bq/L which is much less than observed by Pourchet et al (1997) as shown in Table 6.…”
Section: U and 3 H In Lake Water And Icesupporting
confidence: 80%
“…Papers on rock weathering in the Himalayan region were contributed by Vyshnavi and Islam (2015) and Vyshnavi et al (2013). Vyshnavi and Islam (2015) studied two weathered profiles developed on porphyry granite gneiss and granite gneiss in the Alaknanda valley of the Garhwal Lesser Himalaya.…”
Section: Weathering Erosion Deposition and Provenance Determinationmentioning
confidence: 99%
“…Vyshnavi and Islam (2015) studied two weathered profiles developed on porphyry granite gneiss and granite gneiss in the Alaknanda valley of the Garhwal Lesser Himalaya. By the use of major, trace and rare earth elements the study found that the climate and tectonic milieu was responsible for the development of such weathered profiles in the Himalayan sector.…”
Section: Weathering Erosion Deposition and Provenance Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rocks exposed to abundant rainfall and hot temperatures in tropical regions weather much faster than similar rocks residing in cold and dry regions (Hunt et al, 2021). Low relief of the area results in more water percolation enhancing weathering that is responsible for the destruction/alteration of unstable minerals in regoliths (Fedo et al, 1995;Vyshnavi and Islam, 2015).…”
Section: Introductionmentioning
confidence: 99%